MODELING PRODUCTION PROCESSES USING THE COBB-DOUGLAS FUNCTION (Scientific electronic journal "Labor Economics and Human Capital", 2026)
This paper examines the construction of a Cobb-Douglas production function taking into account two enterprise production factors. The adequacy of the resulting production function with the initial data is verified using the Fisher criterion. The constructed production function is analyzed using indicators of average and marginal resource efficiency, elasticity of output depending on resource consumption, and a forecast of future production volumes is made based on resource combinations. Isoquants and isoclines for the Cobb-Douglas production function are considered.
Keywords: continuously differentiable function, Cobb-Douglas production function, relative increment of function and argument.